Arms and the woman : classical tradition and women writers in the Venetian Renaissance - D'Alessandro Behr, Francesca (Columbus : The Ohio State University Press, 2018)
"Focuses on classical reception in the works of female authors active in Venice during the Early Modern Age. Explores the work of Moderata Fonte and Lucrezia Marinella and demonstrates how they used knowledge of texts by Virgil, Ovid, and Aristotle to promote gender-based egalitarianism"--
Lady knights and pietas -- Women and compassion -- Epic and elegy -- Love and lamentation -- Ancient and modern prototypes -- Away from the city -- Fonte's enchantress and beyond.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed May 7, 2018).
JSTOR
Keywords: Fonte, Moderata, -- 1555-1592 -- Criticism and interpretation; Marinella, Lucrezia, -- 1571-1653 -- Criticism and interpretation; Marinella, Lucrezia, -- 1571-1653; Fonte, Moderata, -- 1555-1592; Italian literature -- Women authors -- History and criticism; Women and literature -- Italy -- History -- 16th century; Women and literature -- Italy -- History -- 17th century; Women -- Italy -- Venice -- History -- 16th century; Women -- Italy -- Venice -- History -- 17th century; Women -- Italy -- Venice -- Social conditions -- 16th century; Women -- Italy -- Venice -- Social conditions -- 17th century; Women -- Italy -- Venice -- History -- Renaissance, 1450-1600.; Femmes et littérature -- Italie -- Histoire -- 16e siècle.; Femmes et littérature -- Italie -- Histoire -- 17e siècle.; Femmes -- Italie -- Venise -- Histoire -- 1450-1600 (Renaissance); Femmes -- Italie -- Venise -- Histoire -- 17e siècle.; Femmes -- Italie -- Venise -- Conditions sociales -- 16e siècle.; Femmes -- Italie -- Venise -- Conditions sociales -- 17e siècle.; LITERARY CRITICISM -- European -- Italian; LITERARY CRITICISM -- General; Italian literature -- Women authors; Women; Women and literature; Women -- Social conditions; Italy; Italy -- Venice; 1500-1699; Criticism, interpretation, etc; History